Penerapan Metode Drill terhadap Peningkatan Kemampuan Menulis Aksara Ulu - Nur Nisai Muslihah; Yeni Asmara (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
This research aims to improve the application of Drill method in enhancing the writing ability of Ulu Script student of Bahasa Indonesia language and literature Education Program STKIP-PGRI Lubuklinggau. The method used in this research is a quantitative descriptive method with the research type of pseudo experiments (quasi experiment). The population in this study is all students of the third semester of the Indonesian Language and Literature Education study Program A and B class of 53 with the sampling is class B that amounted to 26 people. Data collection using an essai-shaped test. The data analysis technique uses t-test. From the results of the study obtained the average value of students after using the Drill method (84.92) is greater than before using the Drill (59.85) method and increased by 25,07. The hypothesis test results showed that at a rate of significance 5% value thit > ttab, 11,61 > 2.78 and 11.61 > 2.06. Conclusion, this means that the application of Drill method can significantly improve the writing ability of the students of Ulu Script Keywords: Drill Methode, Writing, Ulu Script